Friday
March 24, 2017

Post a New Question

Posted by on .

let f(x) =4x^4-6 evaluate f(3)

  • trig - ,

    Raise 3 to the fourth power (giving you 81), multiply the result by 4, and subtract 6 from the result.

    Surely you can do that on your own.

  • trig - ,

    you should be familiar with the terminology of this topic
    if f(x) = 4x^4 - 6
    f(3) = 4(3^4) - 6
    = 4(81) - 6
    = 324-6
    = 318 , (simply replace the x with 3 in the expression)

    BTW, why did you label this question under the topic of "trig" ???

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question